Ensino médio regular noturno: as determinações do capital na formação do trabalhador - Santos, Edvaldo Albuquerque dos (2011)
This study discusses the Regular Night School and the determinations imposed by capital, reflected in the dialectical context of a social classes society. In this context, we are directly related to the daily worker that becomes a student during the night. We draw, in general, the historical process of educational policies in Brazil and Alagoas focused on an unequal society project by its very nature, which is the division of society into classes. We examined the current Law of the Directives and Bases of National Education, No. 9394, 1996, that mentions the provision of secondary education "suitable" to the conditions of the worker. Considering the historicity of the studied object and its constituent elements, as the worker student, the teacher in his or her daily multiple shifts work and the physical and teaching infrastructure of the school, as a result of this study, there are some thoughts to consider : the policies engendered by the neoliberal project determinations represent a high denial process of all the student learning conditions employed; it is noticeable the various high school reforms, the dualism between general education and job training; the conditions of the teacher work (teaching and learning) and the night regular high school student remain significantly precarious, in despite of the official discourse . The theoretical research, in general, presents results linked to the critical positions of the authors researched and points out that the Night Regular School meets the capitalist model requirements, moving decisively away from a school that elevates the human being in its various potentialities. Finally, we have a working class school education with a low teaching and learning quality, result of poor operating conditions.